Tingkat Literasi Digital dalam Pembelajaran Daring di SMP Spring Garden - Ibnu Fiqhan Muslim; Priyono Priyono (Neolectura, 2021)
Internet use continues to increase, in Indonesia internet users with teenagers pay enough attention to it. They use it often to access social media and play online games. continue to learn internet users, especially during the covid-19 pandemic, teaching and learning activities are carried out at home and transformed into bold learning. Various techniques are used to carry out learning boldly, so that learning objectives are still achieved. In addition, parental cooperation is needed to unite learning outcomes that dare to take place from home. With the cooperation of teachers, parents and students during learning, it is hoped that it will not interfere with the efficiency and effectiveness of teaching and learning activities. We can take advantage of the internet by bringing teenagers closer to digital literacy. Based on the phenomena and problems that occur related to the use of the internet by teenagers, this study was conducted to examine how the level of digital literacy competence in bold learning at Spring Garden Middle School is. This study uses quantitative descriptive research methods. Data collection techniques using a questionnaire (questionnaire). Based on the analysis of the data results, it can be said that the level of digital literacy in supporting bold learning is at a grand mean score of 3.04. The score is on a scale range of 2.50-3.25 which indicates that the level of digital literacy skills in supporting e-learning at Spring Garden Junior High School is at a good level.